2019
DOI: 10.1002/ange.201908451
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carboxylic Acids by Palladium‐Catalyzed Hydroxycarbonylation

Abstract: The synthesis of carboxylica cids is of fundamental importance in the chemical industry and the corresponding products find numerous applications for polymers,c osmetics, pharmaceuticals,a grochemicals,a nd other manufactured chemicals.A lthough hydroxycarbonylations of olefins have been knownf or more than 60 years,c urrently knownc atalyst systems for this transformation do not fulfill industrial requirements,for example,stability.Presented herein for the first time is an aqueous-phase protocol that allows c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…The reaction was run for 20 h at 40 °C, and the product was purified by preparative thin-layer chromatography (PTLC) with hexanes/ethyl acetate (3:1) containing 0.8% formic acid to afford 13.7 mg (75%) of 3ad as a white solid. Analytical data were in agreement with literature values 21. 1 H NMR (600 MHz, CDCl3) δ 7.21-7.15 (m, 2H), 7.04-6.91 (m, 2H), 3.26 (h, J = 7.2 Hz, 1H), 2.66-2.41 (m, 2H), 1.30 (d, J = 7.0 Hz, 3H).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The reaction was run for 20 h at 40 °C, and the product was purified by preparative thin-layer chromatography (PTLC) with hexanes/ethyl acetate (3:1) containing 0.8% formic acid to afford 13.7 mg (75%) of 3ad as a white solid. Analytical data were in agreement with literature values 21. 1 H NMR (600 MHz, CDCl3) δ 7.21-7.15 (m, 2H), 7.04-6.91 (m, 2H), 3.26 (h, J = 7.2 Hz, 1H), 2.66-2.41 (m, 2H), 1.30 (d, J = 7.0 Hz, 3H).…”
supporting
confidence: 89%
“…We performed density functional theory (DFT) calculations to study the proposed mechanisms in the hydroarylation of 1a and the origin of the effects of ligand L19 on the anti-Markovnikov regioselectivity ( Figure 2). [21] The O-H oxidative addition pathways using either alcohol or carboxylic acid as the hydride source both require relatively high barriers (TS3 and TS2, ∆G ‡ = 36.3 and 32.1 kcal/mol, respectively). These pathways are disfavored due to the high ligand exchange energy to replace the alkene in the π-alkene complex 8 with n PrOH [22] and the distortion in the intramolecular carboxylic acid O-H oxidative addition, respectively.…”
Section: Scheme 2 Mechanistic Experiments Amentioning
confidence: 99%
“…The results showed that the as‐prepared MOF exhibits outstanding catalytic performance, selectivity, and recyclability in the CO 2 cycloaddition reactions with epoxides. [ 99 ] Theoretically, any MOFs with unsaturated coordination points (monometallic ions, metal clusters, or multi‐metal sites) and potential Lewis acid catalytic activity can be employed to catalyze CO 2 cycloaddition reaction. However, it should be noted that the performance of MOF catalysts will be affected by sorts of factors such as window size, the density of Lewis acid, the synergistic effect of functional sites such as Lewis base sites and nucleophilic sites, framework stability, and reaction conditions, etc .…”
Section: Conversion Of Co2 To Fine Chemicalsmentioning
confidence: 99%
“…[125][126][127] For example, Oxea, BASF, and KH Neochem use a hydroformylation/oxidation sequence to form 3,5,5trimethylhexanoic acid (TMHAc) from di-isobutylene (DIB) in more than 85.000 tons per annum (2017). 128,129 Obviously, a direct hydroxycarbonylation process has advantages in such cases. However, to be industrially viable major improvements are required, especially regarding catalyst stability and recycling.…”
Section: Improved Functional Catalysts For Carbonylation Reactionsmentioning
confidence: 99%
“…With 26 recycling runs this system showed an excellent recycling behavior and provides a basis for a cost-competitive process for manufacturing carboxylic acids. 129 Consequently, as a next step towards realization a continuous mini plant is planned. Another disadvantage of this process is the formation of undesired by-products, e.g.…”
Section: Improved Functional Catalysts For Carbonylation Reactionsmentioning
confidence: 99%